A new strategy for constructing artificial light-harvesting systems: supramolecular self-assembly gels with AIE properties. Issue 23 (7th June 2021) - Ma, Xinxian; Yue, Jinlong; Wang, Yipei; Gao, Yang; Qiao, Bo; Feng, Enke; Li, Zhenliang; Ye, Fei; Han, Xinning
Abstract : An artificial light-harvesting system (ALHS) has been  constructed based on supramolecular organogels, as well as the fluorescent dye rhodamine B (RhB). RhB acted as a good acceptor to realize the energy-transfer process with good efficiency. Abstract : An artificial light-harvesting system (ALHS) has been designed and constructed based on supramolecular organogels made of a simple hydrazide-functionalized benzimidazole derivative (HB), as well as the fluorescent dye rhodamine B (RhB). RhB acted as a good acceptor to realize the energy-transfer process with good efficiency based on a HB/RhB assembly, which showed considerable fluorescence resonance energy transfer (FRET) efficiency of 53% for the energy transfer process. Remarkably, the obtained system showed superior color conversion abilities, converting blue light into orange light. By properly tuning the donor to acceptor ratio, bright orange light emission was achieved with a high fluorescence quantum yield of 35.5%. This system exhibited promise for applications relating to visible-light photo-transformation.